2022
DOI: 10.1002/hpm.3429
|View full text |Cite
|
Sign up to set email alerts
|

The impact of National Centralised Drug Procurement policy on the use of policy‐related original and generic drugs in China

Abstract: Aims To evaluate the effects of the first round of National Centralised Drug Procurement pilot (so‐called ‘4+7’ policy) on the use of policy‐related original and generic drugs. Methods This study used drug purchasing order data from the Centralised Drug Procurement Survey in Shenzhen 2019, covering 24 months from January 2018 to December 2019. ‘4+7’ policy‐related drugs were selected as study samples, including 25 drugs in the ‘4+7’ procurement list and 69 alternative drugs that have an alternative relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
3
13
0
3
Order By: Relevance
“…As a consequence, bid-winning drugs became more dominant in use among the centralized procurement drugs, increasing from 14 to 74%. Also, these results are in line with the body of literature ( Chen et al, 2020 ; Yang et al, 2021a ; Chen et al, 2021 ; Wen et al, 2021 ; Yang et al, 2022a ; Wang et al, 2022 ). In particular, such changes were found to be more prominent in PHCs, compared to those in secondary and tertiary hospitals, which indicated that the bid-winning drugs among the centralized procurement drugs may be more reflective to the drug demands at PHC level.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…As a consequence, bid-winning drugs became more dominant in use among the centralized procurement drugs, increasing from 14 to 74%. Also, these results are in line with the body of literature ( Chen et al, 2020 ; Yang et al, 2021a ; Chen et al, 2021 ; Wen et al, 2021 ; Yang et al, 2022a ; Wang et al, 2022 ). In particular, such changes were found to be more prominent in PHCs, compared to those in secondary and tertiary hospitals, which indicated that the bid-winning drugs among the centralized procurement drugs may be more reflective to the drug demands at PHC level.…”
Section: Discussionsupporting
confidence: 92%
“…The procurement data extracted from the CDSIP database include drug name, the name of medical institution, procurement date, dosage form, specification, packaging, manufacturer, unit price, procurement unit (by box, bottle, or branch), procurement quantity, procurement expenditures, etc. In the present study, we selected “4 + 7”-related drugs as study samples ( Wang N. et al, 2021 ; Yang et al, 2022a ; Wang et al, 2022 ), which were defined as drug INNs in the “4 + 7” procurement List (“4 + 7” List drugs) as well as their alternative drugs that have not yet been covered by the “4 + 7” procurement policy. Next, the identification of alternative drugs followed the definition of the NHSA in the Monitoring Plan for Centralized Drug Procurement and Use Pilot Work ( NHSA, 2019b ), which refers to the clinically substitutable drugs of the same kind with “4 + 7” List drugs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of HCPs and healthcare regulatory practitioners supported biosimilars utilization if they were covered by the Chinese centralized drug procurement program ( Wang et al, 2021 ). It is shown that this aforementioned policy promoted the use of generics and had positive effects on drug price cut and medication burden reduction ( Yang et al, 2022 ). Similarly, uptake of biosimilars and control of medical costs might also gain benefit if biosimilars could be selected in centralized procurement program.…”
Section: Discussionmentioning
confidence: 99%